Investigation of combustion patterns in furnace type chemical reactor with non-stoichiometric combustion of fuel in the Ansys CFX software package - P. A. Batrakov; D. G. Mumladze (Омский научный вестник)
The paper considers the calculation of the combustion chamber of a chemical reactor in the software complex Ansys CFX, which allows to determine the thermal characteristics, as well as the concentration of CO, CO2 at the output with different air flow coefficients. The paper presents the computational model, the initial conditions, and describes the calculation algorithm and the formation of the diffusion scheme. Verification of the methodology for adequacy when comparing the numerical model in ANSYS CFX with the literature data, which showed a maximum discrepancy of 6,92 %. Calculations shows that the operating mode of the reactor will be observed for 1.